2012
DOI: 10.1111/j.1540-4781.2012.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Task Involvement Load on L2 Incidental Vocabulary Learning: A Meta‐Analytic Study

Abstract: This meta‐analytic study provides a systematic statistical synthesis of the effects of output tasks on second or foreign incidental vocabulary learning. A total of 12 studies were included in this meta‐analysis. Five mediator variables were examined: design quality, types of output task, time on task, genres of text, and text–target word ratios. Results show that language learners who completed an output task outperformed those who only read a text. Results also support the involvement load hypothesis: Languag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
40
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(48 citation statements)
references
References 31 publications
6
40
1
1
Order By: Relevance
“…Laufer and Hulstijn (2001) discuss the Involvement Load Hypothesis, which refers to the cognitive and motivational weight of vocabulary tasks. Based on this hypothesis, Kim (2008) concludes that there is a connection between motivation and lexical performance; a meta-analysis conducted by Huang, Eslami, and Wilson (2012) confirms this finding. For example, these authors found that language learners who completed an output task outperformed those who only read a text, and language learners who performed a task with a higher degree of involvement load gained more vocabulary.…”
Section: L2 Receptive Vocabulary Knowledgesupporting
confidence: 48%
“…Laufer and Hulstijn (2001) discuss the Involvement Load Hypothesis, which refers to the cognitive and motivational weight of vocabulary tasks. Based on this hypothesis, Kim (2008) concludes that there is a connection between motivation and lexical performance; a meta-analysis conducted by Huang, Eslami, and Wilson (2012) confirms this finding. For example, these authors found that language learners who completed an output task outperformed those who only read a text, and language learners who performed a task with a higher degree of involvement load gained more vocabulary.…”
Section: L2 Receptive Vocabulary Knowledgesupporting
confidence: 48%
“…Different L2 learning activities require different amounts of these motivational (need) and cognitive (search, evaluation) constructs, and activities that require a higher involvement from the learner are expected to lead to more learning. A meta-analysis by Huang, Willson, and Eslami (2012) found support for this hypothesis: Participants who completed an output task (which supposedly was high in involvement) acquired more vocabulary than those who only read a text (which supposedly was low in involvement).…”
Section: Mechanisms Of Incidental Learningmentioning
confidence: 99%
“…However, when the same tasks were repeated, taskinduced involvement load is not related to further improvement. Independently, Huang, Eslami, and Willson (2012) revealed that word leaning is better in the learners who read a combination of expository and narrative texts than those who read either of an expository or narrative text. However, when time spent on the tasks is considered, the benefits connected to a higher degree of task-induced involvement load faded.…”
mentioning
confidence: 99%